Insurgent Compensation: Evidence from Iraq - Bahney, Benjamin W; Iyengar, Radha K; Johnston, Patrick B; Jung, Danielle F; Shapiro, Jacob N; Shatz, Howard J (American Economic Review, 2013)
Participating in insurgency is physically risky. Why do people do so? Using new data on 3,799 payments to insurgent fighters by Al Qa'ida Iraq, we find that: (i) wages were extremely low relative to outside options, even compared to unskilled labor; (ii) the estimated risk premium is negative; and (iii) the wage schedule favors equalization and provides additional compensation for larger families. These results challenge the notion that fighters are paid their marginal product, or the opportunity cost of their time. They may be consistent with a “lemons” model in which fighters signal commitment by accepting low wages.